National Consensus on Management of Non-Variceal Upper Gastrointestinal Tract Bleeding in Indonesia - The Indonesian Society of Gastroenterolo The Indonesian Society of Gastroenterology (Acta Medica Indonesiana, 2016)
he Indonesian Society of Gastroenterology has compiled a national consensus guideline for the management of non-variceal upper gastrointestinal bleeding (NVUGIB). It is an endeavor to raise the quality of service for NVUGIB patients associated with peptic ulcer. The references for developing this consensus include three recent consensus guidelilnes on the management of NVUGIB and a modification of Delphi process was done to develop clinical guidelines. The three references are: The International Consensus Recommendations on the Management of Patients with Non-variceal Upper Gastrointestinal Bleeding (ICON-UGIB), 2010; Asia-Pacific Working Group consensus on non-variceal upper gastrointestinal bleeding, 2011; and Management of Patients with Ulcer Bleeding, ACG guidelines, 2012. The consensus is compiled as a reference for Indonesian medical practitioners all across the country on the management of patients with non-variceal upper gastrointestinal bleeding associated with peptic ulcer. However, the technical implementation extremely depends on diagnostic and therapeutical facilities available in each health care center.